Thiazole-Scaffold-Based Anti-tubercular Agents: A Review on Synthesis and Structural Modifications - Kumar, Ankur; Debnath, Utsab; Roy, Kuldeep K. (Synlett, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a major global health challenge due to the rise of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains. The urgent need for novel anti-tubercular agents has driven extensive research in heterocyclic scaffolds, with thiazole-based compounds emerging as promising candidates. Thiazole-based compounds exhibit potent anti-tubercular activity by targeting key bacterial enzymes, disrupting cell wall synthesis, and interfering with essential metabolic pathways. Thiazole ring compounds show significant biological activity due to their versatile chemical nucleophilic and electrophilic reactivity. This review provides a comprehensive analysis of the conventional and modern synthetic approaches for thiazole-scaffold-based anti-tubercular agents. Additionally, it explores structural and functional group modifications on the thiazole core and their impact on anti-tubercular activity. Recent advancements in molecular modeling, hybrid molecule design, and medicinal chemistry strategies for optimizing thiazole derivatives are also discussed. The insights presented in this review highlight the potential of thiazole scaffolds in TB drug discovery and underscore the need for further medicinal chemistry, preclinical and clinical investigations to develop effective and safer TB therapeutics.1 Introduction1.1 Chemical Reactivity of the Thiazole Ring1.2 Different Conventional Methods Used for the Synthesis of Substituted Thiazoles as Anti-tubercular Agents1.2.1 Hantzsch Thiazole Synthesis1.2.2 Gabriel Synthesis1.2.3 Cook–Heilbron Synthesis1.2.4 Other Reported Methods2 Small Molecule Inhibitors (SMIs) as Anti-tubercular Agents2.1 Phenyl-thiazole Derivatives2.2 Imidazo[2,1-b]thiazoles2.3 Carbazolo-thiazole Derivatives2.4 Thiazole-chalcone Derivatives2.5 Bis-thiazole Derivatives2.6 2,4,5-Trisubstituted Thiazole Derivatives2.7 Hydrazine-thiazole Derivatives2.8 Thiazolidinone Derivatives2.9 Carboxamide-thiazole Derivatives2.10 Benzothiazole Derivatives2.11 Amino-thiazole Derivatives2.12 Thiazole-thiadiazole Derivatives2.13 Thiazole-coumarin Derivatives2.14 Pyrazolyl-thiazole Derivatives2.15 Sulfonyl-thiazole Derivatives2.16 Summary of Anti-tubercular Targets in Section 23 Molecular Modeling Analysis4 Challenges of Mutations and Future Perspectives5 Recent Advances in Clinical Trials for Anti-tubercular Drug Development6 Conclusion
Keywords: tuberculosis; drug resistance; thiazole scaffold; medicinal chemistry; Mycobacterium tuberculosis